NEXT MOVE (Computer Weekly, 2003)
My other skills include SQL, Unix shell scripting, C and C++, Perl, HTML and Javascript. I am finding it difficult to secure a job interview as most companies ask for Java or C++. Although I am revising my C++ skills, the training courses are very expensive. What should I do?